Hubungan Antara Pengurusan Perubahan dan Kejayaan Sistem Maklumat di PDRM - Rizal, Abd Rahman Sidek (2011)
This study which was done in Kuala Lumpur Traffic Police Branch is to represent the agency of the Royal Malaysia Police (RMP). The study undertaken is intended to see the extent of the relationship between the change management and the success of information system in the police organization as an attempt to provide better service to customers. The study is looking at the change management involving three (3) important factors which include attitude, skills and communication as well as information systems success elements which consist of information quality, system quality and service quality. A total of 200 questionnaires were distributed at the study site and a total of 179 or 89.5% of the respondents were police officers. The data obtained was analyzed by using statistical research software which known as Statistical Package for Social Science (SPSS) version 17.0. The study found that in studying the relationship between attitudes, skills, and communication with the success of information systems using correlation and multiple regression tests, only two factors have significant influence which are attitudes and communication factors. The respondents of the study show good level of attitudes, skills and communications which means that police organizations have all the three factors in ensuring the police information system. Similarly, in term of the information system success the study found that the police information system can be considered successful. With these findings, it will help the police to plan strategies that can be used in improving existing systems in order to enhance the success of information systems, thus provide the best service to the people and country.